Green and Convenient One-Pot Access to Polyfunctionalized Piperidine Scaffolds via Glutamic Acid Catalyzed Knoevenagel- Intramolecular [4+2] aza-Diels-Alder Imin-Based Multi-Component Reaction Under Ambient Temperature. (26th May 2020) - Mohamadpour, Farzaneh
ABSTRACT: A catalytic methodology is reported that enables the green, operationally simple and convenient synthesis of corresponding polyfunctionalized piperidine scaffolds via one-pot Knoevenagel- intramolecular [4+2] aza-Diels-Alder imin-based multi-component reaction of between β-ketoesters, aromatic aldehydes and various amines, including some relevant drugs and pharmacologically active derivatives in the presence of biologically active α-amino acid, glutamic acid as a green and biodegradable catalyst. Remarkable E factors, green, readily and inexpensive catalyst, short reaction times, high to excellent yields, mild reaction conditions, high atom-economy and easy isolation procedures are key features of this methodology.